Separation, Isolation and Alienation in the Novels of Jaishree Misra - Rani, N. Sharmila; Benny, N. Solomon (Advances in Social Sciences Research Journal, 2023)
The novels written by Jaishree Misra are all about the author’s perspectives on life. She asserts that all of her writings reveal some degree of autobiographical foundations, as she selects some momentous occurrences from her own life or from the lives of others and then spurs them to create a larger reality in fiction. Misra’s works cover a wide variety of topics, and the author is unrelenting in her exploration of the challenges that face women and the impact of diasporic experiences on Indian cultural traditions. However, the female characters in her novels struggle to understand their selves and develop into alienated creatures as a result of this struggle. The women characters who appear in some of Misra’s novels are touched upon in this paper.